Low-Complexity Resource Allocation for Downlink Multicarrier NOMA Systems - Wang, Chin-Liang; Chen, Tzu-Ying; Chen, Yung-Fang; Wu, Dong-Shing (IEEE International Symposium on Personal, Indoor, and Mobile Radio Communications workshops (Print), 2018)
In this paper, we investigate resource allocation for a downlink multicarrier non-orthogonal multiple access (NOMA) system with a base station and an even number of users, where every two users are grouped together to share some subcarriers for data transmission. We formulate an optimization problem in terms of subcarrier and power allocation to maximize the system capacity under a specific proportional user fairness constraint. For a given subcarrier allocation, we first derive an optimal power allocation factor for two users on a subcarrier subject to maximizing the minimum user capacity on the subcarrier. With such optimal power allocation factors for all subcarriers, a low-complexity suboptimal algorithm is then proposed for joint subcarrier and power allocation to meet the proportional user fairness constraint. Simulation results demonstrate that the proposed scheme provides better system capacity than the conventional orthogonal frequency division multiple access (OFDMA) scheme.